證據說了什麼？國民中小學教師專業發展的樣貌 What does the Evidence Say? The Landscapes of Professional Development of Teachers in Elementary and Junior High Schools - 孫志麟 Chih-Lin Sun (National Changhua University of Education, 2022)
教師專業發展是提升教師素質與教學專業的關鍵。國際組織和世界各國陸續提出有關教師專業發展的政策、方案或措施，期能確保教學專業，增進學生學習成就。本研究運用經濟合作暨發展組織進行的《國際教學與學習調查》資料，以 TALIS 2018 數據為基礎，進行次級資料的解讀與分析，探討臺灣國民中小學教師專業發展的樣貌。研究發現：一、國民中小學教師普遍參與專業發展活動，其參與類型是以專題研討、參與教師社群、教育議題介紹等活動居多，而較少進行與證照取得有關的專業學習活動。二、國民中小學教師專業發展的內容是以學科知識、學科教學知識、課程知識為主，而對於跨文化溝通、文化回應教學議題則較少參與。三、國民中小學教師專業發展的效應展現在建立專業知識、促進專業協作、教學實踐應用等方面，但卻未能促進教學專業的永續發展。四、國民中小學教師專業發展的阻礙主要是來自於工作忙碌、時間不足、缺乏誘因、沒有適切的專業發展活動等等。整體來看，臺灣國民中小學教師專業發展並不亞於 TALIS 調查結果的平均水準。不過，教師專業發展在臺灣的實踐，仍有其薄弱環節與問題尚待克服。據此，臺灣國民中小學教師專業發展政策之推展，必須持續創造教師協作及網絡連結的文化氛圍，加強教師跨文化溝通素養與文化回應教學能力，重視教師專業發展成效評估與永續發展，以及建構完善的教師專業發展支持系統。 Teacher professional development is the key to improving teacher quality and teaching profession. International organizations and countries around the world have proposed policies, programs, or strategies related to the professional development of teachers. This study employed data from the Teaching and Learning International Survey (TALIS) conducted by the Organization for Economic Cooperation and Development (OECD). Based on TALIS 2018 evidence, it analyzed the landscapes of professional development of teachers in elementary and junior high schools in Taiwan. The research results are as follows. 1. The types of professional development of teachers include thematic seminars, participation in teacher communities, and introduction of educational issues, but less professional learning activities are related to obtaining licenses. 2. The contents of professional development of teachers are subject knowledge, subject teaching knowledge, and curriculum knowledge, and they have less participation in cross-cultural communication and culturally responsive teaching issues. 3. The effects of professional development of teachers are shown in the establishment of professional knowledge, promotion of professional collaboration, and application of teaching practice, but these have failed to promote the sustainable development of the teaching profession. 4. The obstacles to the professional development of teachers mainly come from busy work, insufficient time, lack of incentive, and no appropriate professional development activities. Overall, the professional development of teachers in Taiwan is no less than that in the countries participating in the TALIS survey, but there are still weak points and problems to be overcome. Based on these results, the policy and practice of teacher professional development in Taiwan should help create a cultural climate of teacher collaboration and network connection, and strengthen the cultivation of cross-cultural communication literacy and cultural response teaching competency of teachers. Furthermore, effectiveness evaluation and sustainable development should be emphasized, and support systems for teacher professional development should be built.